Exploited but Unevaluated: DNA Barcoding Reveals Skates and Stingrays (Chordata, Chondrichthyes) Species Landed in the Indonesian Fish Market - Hawis Madduppa; Rani Utari Ayuningtyas; Beginer Subhan; Dondy Arafat; Prehadi . (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Reliable and precise species identification is important to fisheries management and conservation. However, many rays and skates in Indonesia are currently being exploited and landed into traditional fish market without a proper identification. Therefore, this study was conducted to identify species of skates and stingrays that were landed and traded in three fish markets in Indonesia (Palabuhanratu, Muara Saban, and Lampung) using molecular techniques and to determine the conservation status of the identified species based on IUCN (International Union for Conservation of Nature and Natural Resources) as well as defined by CITES (Convention on International Trade in Endangered Species). The mitochondrial cytochrome oxidase I (COI) gene was amplified by polymerase chain reaction (PCR) using a pair of primer, fish-BCL and fish-BCH. Of 29 tissue samples collected from the study sites, a total of five species were successfully identified: Dipturus chilensis (4), Himantura walga (1), Neotrygon kuhlii (11), Taeniura lymma (9) and Rhinoptera javanica (4). The Neighbor Joining phylogeny of mitochondrial lineages, based on partial COI gene sequences, the ingroup haplotypes were clustered into five main clades representing each species. The identified stingrays were being listed as vulnerable (D. chilensis and R. javanica), near threatened (H. walga and T. lymma), and data deficient (N. kuhlii) by IUCN, with two species (D. chilensis and H. walga) population were indicated decreased. Unfortunately, all of identified species have not been evaluated by CITES regarding their trade status. As a consequences, a valuable effort should be placed to create a scientific network for monitoring programmes not only on a local scale, and to make pressure on governments for adopting molecular techniques as tools for controlling and avoiding misidentification. Keywords: Mitochondrial DNA, Phylogeny, Coral Triangle, Taxonomy, Fisheries